Peran Manajemen Risiko dalam Logistik pada Manajemen Rantai Pasokan: Dwelling Time di Pelabuhan - Putri, Marini Andriyani (Peneliti.net, 2024)
Risk management plays a crucial role in logistics and supply chain management, especially in the context of dwelling time at ports. Dwelling time, the time required for goods to stay at a port from arrival to departure, affects operational efficiency and logistics costs. At Tanjung Priok Port, prolonged dwelling time issues are caused by inadequate infrastructure, slow customs mechanisms, and poor coordination among related agencies. This study examines the impact of dwelling time on loading and unloading efficiency and its implications for national logistics costs. High dwelling time adds to logistics costs and harms various parties, including container terminal operators and logistics companies. Moreover, long dwelling time reduces national competitiveness by slowing down the flow of goods and increasing uncertainty in the supply chain.Through a risk management approach, this research identifies key risk sources affecting dwelling time and proposes mitigation strategies to reduce their impact. These strategies include improving port infrastructure, enhancing information technology systems to facilitate customs processes, and strengthening coordination among agencies. Effective risk management implementation is expected to reduce dwelling time, enhance port operational efficiency, and decrease overall logistics costs, thereby boosting Indonesia’s competitiveness in global trade. This study provides valuable insights for policymakers, port operators, and logistics practitioners regarding the importance of risk management in addressing dwelling time issues. Thus, it is hoped that a more efficient and resilient supply chain can be created to address various uncertainties and challenges in the future.